2020
DOI: 10.1186/s12970-020-00349-6
|View full text |Cite
|
Sign up to set email alerts
|

CYP1A2 genotype and acute effects of caffeine on resistance exercise, jumping, and sprinting performance

Abstract: Background: It has been suggested that polymorphisms within CYP1A2 impact inter-individual variation in the response to caffeine. The purpose of this study was to explore the acute effects of caffeine on resistance exercise, jumping, and sprinting performance in a sample of resistance-trained men, and to examine the influence of genetic variation of CYP1A2 (rs762551) on the individual variation in responses to caffeine ingestion.Methods: Twenty-two men were included as participants (AA homozygotes n = 13; C-al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 42 publications
(86 reference statements)
3
53
0
3
Order By: Relevance
“…17 Interestingly, a recent study found that CAF improves jump performance in resistance-trained men, but this improvement was independent of CYP1A2 genotypes. 36 Together, our findings and those in the reviewed literature indicate that CAF may be ergogenic for jump performance in some circumstances, but it seems to be independent of CYP1A2 genotype.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…17 Interestingly, a recent study found that CAF improves jump performance in resistance-trained men, but this improvement was independent of CYP1A2 genotypes. 36 Together, our findings and those in the reviewed literature indicate that CAF may be ergogenic for jump performance in some circumstances, but it seems to be independent of CYP1A2 genotype.…”
Section: Discussionsupporting
confidence: 70%
“…Contradictory findings in relation to the influence of CYP1A2 genotypes on CAF‐induced improvements in muscular endurance have been reported, with one study showing an increased number of repetitions (85% of 1RM performed until failure) after CAF ingestion only in AA homozygotes (n = 14) 14 . In another study, CAF improved muscular endurance to a similar degree in both AA homozygotes and C allele carriers 36 . No prior study has investigated the effect of CAF ingestion separately in AC and CC genotype, so our findings expand our understanding by showing that CAF improves muscular endurance in all three variants of the CYP1A2 polymorphism.…”
Section: Discussionmentioning
confidence: 94%
“…In the current investigation, acute caffeine intake (3 mg•kg −1 •bm) was effective to increase jump height in a countermovement jump (+3.9%). This ergogenic effect of caffeine is a recurrent finding in the literature as several investigations have found an effect of similar magnitude in basketball players [11], volleyball players [49], swimmers [13], and resistance-trained individuals [31]. Acute caffeine intake was also ergogenic to enhance sprint performance as it reduced the time to complete a 30-m sprint test (−2.6%).…”
Section: Cyp1a2mentioning
confidence: 67%
“…However, to date, findings have been controversial, with some studies reporting a higher response to caffeine in AA athletes [22,29] and other studies showing a better response to caffeine in C-carrier athletes [30]. Overall, most of the investigations have found that the ergogenic response to caffeine is independent of the CYP1A2 −163 C > A polymorphism [11,23,24,[31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…The results indicate that the caffeine intake increased the peak power (±682 W vs. ±667 W; p = 0.008) and the mean power during the Wingate test (±527 W vs. ±518 W; p < 0.001) without differences between A/A genotype and C-allele carriers (p > 0.05). These appointments were again confirmed by Grgic et al (2020b) using the same dosage of caffeine (3 mg.kg −1 ) in the morning before the Wingate test. Thus, there is no evidence that different genotyping for CYP1A2 can mediate increased performance from caffeine use in short duration, high-intensity exercises, at least in the doses used (3-6 mg.kg −1 ).…”
Section: Adora2a Gene Rs5751876 Polymorphismmentioning
confidence: 86%